Compassion Practices and HCAHPS: Does Rewarding and Supporting Workplace Compassion Influence Patient Perceptions?. (19th May 2014) - McClelland, Laura E.; Vogus, Timothy J.
<x xml:space="preserve">Abstract</x> Objective To examine the benefits of compassion practices on two indicators of patient perceptions of care quality—the Hospital Consumer Assessment of Healthcare Providers and systems (HCAHPS) overall hospital rating and likelihood of recommending. Study Setting Two hundred sixty‐nine nonfederal acute care U.S. hospitals. Study Design Cross‐sectional study. Data Collection Surveys collected from top‐level hospital executives. Publicly reported HCAHPS data from October 2012 release. Principal Findings Compassion practices, a measure of the extent to which a hospital rewards compassionate acts and compassionately supports its employees (e.g., compassionate employee awards, pastoral care for employees), is significantly and positively associated with hospital ratings and likelihood of recommending. Conclusions Our findings illustrate the benefits for patients of specific and actionable organizational practices that provide and reinforce compassion.